Islamic Instructional Leadership Practices in Madrasah Ibtidaiyah - Hamdanah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This study explores Islamic instructional leadership practices implemented by Madrasah Ibtidaiyah principals and their impact on teacher performance. Employing a qualitative approach with multiple case study design, the research involved madrasah principals, teachers, and supervisors from three to five purposively selected Madrasah Ibtidaiyah. Data were collected through in-depth interviews, participant observation, document analysis, and focus group discussions, then analyzed using reflexive thematic analysis. Findings identified five dimensions of Islamic instructional leadership: spiritual-moral, vision and mission of learning, supervision and mentoring, professional development, and instructional management. The spiritual-moral and supervision-mentoring dimensions proved most influential on teacher performance, creating intrinsic motivation through awareness of sacred trust and enhancing competence through a familial approach. Islamic instructional leadership impacts lesson planning, instructional delivery, and assessment through mechanisms of enhanced spiritual motivation, professional competence development, collaborative culture, and conducive organizational climate. This research enriches educational leadership literature with Islamic perspectives and offers practical models for improving madrasah leadership quality. Theoretical implications include developing leadership frameworks integrating spiritual and professional dimensions, while practical implications provide guidance for madrasah principals and policymakers in developing mentoring programs aligned with Islamic values.